1995
DOI: 10.1037/0278-7393.21.6.1539
|View full text |Cite
|
Sign up to set email alerts
|

Estimation strategies and the judgment of event frequency.

Abstract: Processes underlying judgments of absolute event frequency were investigated in 3 experiments. In all 3, word pairs consisting of a target (a category label, e.g., CITY) and context (a category exemplar, e.g., London) were presented in a different-or same-context study list. In the different-context condition, each target was paired with a new context on each presentation; in the same-context condition, a target always appeared with the same context. Verbal protocols (Experiment 1) and response times (Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
157
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(173 citation statements)
references
References 77 publications
12
157
4
Order By: Relevance
“…Finally, an analogue to adjusted retrieval has been seen in the lab. Here it is common for participants to generate frequency estimates by retrieving some subset of relevent instances and then adjusting their enumerated counts to account for the unretrieved items (Brown, 1995). Thus, although numerical strategies appear to be uncommon in many realworld estimation tasks, people can and do retrieve, adjust, and transform numerical values when they are available.…”
Section: The Numerical Retrieval Modementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, an analogue to adjusted retrieval has been seen in the lab. Here it is common for participants to generate frequency estimates by retrieving some subset of relevent instances and then adjusting their enumerated counts to account for the unretrieved items (Brown, 1995). Thus, although numerical strategies appear to be uncommon in many realworld estimation tasks, people can and do retrieve, adjust, and transform numerical values when they are available.…”
Section: The Numerical Retrieval Modementioning
confidence: 99%
“…On the other hand, because real-world knowledge is complex, and relevant between-domain differences are large, estimation strategies vary from task to task, and different strategies often compete within the same task. It follows that the study of real-world estimation should produce information about the range of estimation strategies people use, the factors that influence strategy selection, and the ways that people coordinate competing sources of information (Brown, 1995(Brown, , 1997Brown & Siegler, 1993;Conrad, Brown, & Cashman, 1998). In brief, because performance on many real-world estimation tasks reflects the systematic interplay of process and content, it is possible to employ these tasks to investigate both.…”
mentioning
confidence: 99%
“…We have called this the multiple strategy perspective (Brown, 1995(Brown, , 1997(Brown, , 2002Conrad, Brown, & Cashman, 1998). The basic idea is that, although many strategies are potentially available, Some of the material contained in this article was presented at the 1999 conference of the American Association for Public Opinion Research.…”
Section: The Multiple Strategy Perspective On Frequency Estimationmentioning
confidence: 99%
“…We (Brown, 1995(Brown, , 1997Conrad et al, 1998) have observed people using all of these strategies when the test categories were familiar (e.g., cities, musical instruments, and trips to the grocery store) and probably matched people's encoding of events (this match was ensured for laboratory participants by presenting events that consisted of an instance and its category, the same category on which participants were later tested). But on what basis do people respond when they have not encoded the events as instances of the test categories, presumably because the instances fit more naturally with other categories?…”
Section: The Multiple Strategy Perspective On Frequency Estimationmentioning
confidence: 99%
See 1 more Smart Citation